Maritime Transport Costs and Port Efficiency - Clark, Ximena; Dollar, David; Micco, Alejandro (World Bank, Washington, DC, 2013)
Recent literature has emphasized the importance of transport costs and infrastructure in explaining trade, access to markets, and increases in per capita income. For most Latin American countries transport costs are a greater barrier to U.S. markets than import tariffs. The authors investigate the determinants of the costs of shipping to the United States using a large database (more than 300,000 observations a year) on shipments of products at the six-digit level of the Harmonized System of classification from different ports around the world. They find that distance and containerization matter. They find that the efficiency of ports is also important. Improving the efficiency of a port from the 25th to the 75th percentile reduces shipping costs by 12 percent. (On average, having bad ports is equivalent to being 60 percent farther away from markets.) Inefficient ports also increase handling costs, which are part of shipping costs. Finally, the authors try to explain variations in port efficiency. They find that the variations are linked to excessive regulation, the prevalence of organized crime, and the general condition of the country's infrastructure.